Pigs make me sneeze! : an elephant & piggie book - Willems, Mo (New York : Hyperion Books for Children, 2009)
Gerald believes he is allergic to his best friend! Will he have to stay away from Piggie forever?
1.3
Keywords: Swine -- Juvenile fiction; Elephants -- Juvenile fiction; Friendship -- Juvenile fiction; Fantasy; Readers (Elementary)